López Aliaga and Popular Renewal: A patriarchal restoration project - Vildoso Chirinos, Carmen (2022)
This article is dedicated to analyze the political project condensed in the Popular Renewal party under the leadership of businessman Rafael López Aliaga. A period that covers three electoral processes in three consecutive years is examined: extraordinary elections to Congress, national elections and municipal elections. López Aliaga, who is disputing the leadership of the opposition to Keiko Fujimori, is the representative of an extremely conservative right, which amalgamates politics and religion. This article delves into the proposed government plan submitted to the national elections, comparing it to the proposals of other right-wing sectors, as well as the profile of its social base. It becomes evident that, in the definition of the current political coordinates, alongside the positioning against the democratic system or the economic models, issues such as gender equality become especially relevant. As a result of his election as mayor of Lima, the double risk represented by the opposition between the mayor´s office and the Presidency of the Republic, and the coincidence between the two in terms of political conservatism is raised.